Manajemen Akademik dan Kualitas Pendidikan: Sebuah Kajian Mendalam Membagun Kepemimpinan - Hasan Basri; Nurhayuni Nurhayuni; Parisyi Algusyairi; Muhammad Syaifuddin (LP. Ma'arif Janggan Magetan, 2023)
The aim of this research is to conduct an in-depth study of the relationship between academic management and educational quality with a focus on leadership development. The preparation of this work used the literature review method by searching for data via Google Scholar and Sinta using the keyword principal leadership. The five identification steps include interpreting the scope of the topic, identifying relevant sources, reviewing the literature, writing a review, and applying the literature to the study, with data from six articles analyzed qualitatively. The results of the work emphasize a) the importance of visionary academic leadership with the support of leadership theory to formulate educational direction and achieve quality goals. b) The integration of management concepts, academic engagement, and collective collaboration in educational leadership provides inspiration for continuous improvement and educational excellence. c) Academic leaders must be adaptive strategic decision makers, maintain optimal educational quality, and ensure the positive contribution of educational institutions to society. d) The importance of establishing an organizational culture that supports improving the quality of teaching and staff performance in a conducive work environment. e) Facing contemporary challenges, academic leaders need to have a strategic vision, a balance between leadership and management, and the ability to manage resources to respond to the rapid dynamics of the times.